Performance Of Fire-Damaged Reinforced Concrete Rectangular Columns Retrofitted With Fiber Reinforced Polymer Composites - Moghtadernejad, Nima (2014)
In this experimental study, a total of twenty-one rectangular RC columns have been prepared and tested under axial compression test in three groups: un-heated, heated, heated-and-repaired with FRP. The objectives of the study were firstly to study the effect of fire temperature at 500°C and 600°C on the compressive strength and secant axial stiffness; and secondly to study the effect of repairing with GFRP and CFRP including the number of layers on improvement in compressive strength and axial stiffness, of RC columns. The RC columns were exposed to fire with the method of steady-state test under temperatures of 500°C and 600°C. The heated RC columns were repaired with unidirectional CFRP and GFRP jackets in one and two layers for the purpose of investigating the improvement in the compressive strength and the secant axial stiffness of the rectangular RC columns. The experimental results show that the residual compressive strength of RC columns were 43.1 % and 34% of the compressive strength of un-heated RC columns after being exposed to temperatures of 500°C and 600°C, respectively.